Vulnerabilidades de segurança e contramedidas em plataformas MPSoCS - Sant’Ana, Anderson Camargo (2019)
Computer systems tend to adopt parallel architectures, using Multi-Processor Systems-on-Chip (MPSoCs). MPSoCs are vulnerable to software and hardware attacks, such as infected applications and Hardware Trojans that can be installed on an MPSoC. The goal of these attacks can be the access sensitive data, disrupting a particular application, or even physically damaging the system. The literature presents several countermeasure techniques: the use of dedicated routing algorithms, encryption, firewalls, filters, and secure zones. These approaches have an important hardware cost (firewalls or encryption) or are very restrictive to the use of MPSoC resources (secure zones). The objective of this Dissertation is to implement the attacks to expose the vulnerabilities presented in MPSoC platforms and propose lightweight security mechanisms for the vulnerabilities. MPSoCs can be attacked both at the hardware and software levels. These attacks compromise the integrity of the data processed by the system. Among the vulnerabilities studied stands out: (i) communication API; (ii) operating system; (iii) network infrastructure; (iv) access to memory; (v) installation of Hardware Trojans. The lightweight security mechanisms for MPSoCs presented in this work adopt four techniques: spatial isolation of applications; dedicated network to send sensitive data; firewall to block malicious traffic using filters; cryptography. These mechanisms protect the MPSoC against the most common software attacks, such as Denial of Service (DoS) and man-inthe- middle, ensuring confidentiality and integrity to applications. Results show low area overload and latency, which are justified by the added security in MPSoCs.